Cognitive Level Analysis of English Semester Test for Grade X State Senior High Schools in Bukittinggi - Nadya Ismah Khairunnisa; M. Zaim (Universitas Negeri Padang, 2023)
This study aimed to explore the cognitive level of questions used by teachers on English semester tests for grade X academic year 2021/2022 at senior high schools in Bukittinggi and the problem faced by English teachers at senior high schools in Bukittinggi in constructing HOTS questions test. This research conducted by using descriptive method. The writer chose five senior high schools in Bukittinggi: SMAN 1 Bukittinggi, SMAN 2 Bukittinggi, SMAN 3 Bukittinggi, SMAN 5 Bukittinggi, and SMAN 5 Bukittinggi. In collecting the data, the writer used the document analysis and interview. From the data analysis, the writer found that English semester test made by teachers at senior high schools contained less HOTS questions where its only cover 12,9% or 23 questions out of 177 total questions. Lack of understanding and students’ readiness in receiving HOTS questions become the problem that faced by teachers in designing HOTS questions. According to the findings, the writer suggests teachers be more often involve HOTS questions into semester test. In addition, teachers should be provided with proper training related to HOTS in order to help teacher to be more familiar with designing HOTS questions.